2002
DOI: 10.1007/s00213-002-1086-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the discriminative stimulus effects of N -methyl- D -aspartate ligands under different ethanol training conditions in the cynomolgus monkey ( Macaca fascicularis )

Abstract: These data suggest that NMDA receptor-mediated activity is a component to the discriminative stimulus effects of ethanol in male and female nonhuman primates. However, NMDA uncompetitive antagonists were less likely to produce discriminative stimulus effects similar to a high ethanol training dose in male monkeys. In comparison to consistent substitution by GABA(A) positive modulators for ethanol, substitution patterns produced by NMDA uncompetitive antagonists suggest a less robust mediation of the ethanol di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…A greater proportion of the ethanol stimulus may involve receptors sensitive to 3␣-hydroxysteroids in monkeys trained to discriminate lower compared with higher doses of ethanol. In support of this hypothesis, NMDA receptors appear to mediate the discriminative stimulus effects of 2.0 g/kg ethanol in female monkeys (Vivian et al, 2002), the group showing the lowest efficacy of GABA A receptor-sensitive neuroactive steroids in this study. However, the NMDA receptor antagonist 3␣,5␤-P HS (Park-Chung et al, 1997) did not substitute for ethanol in any group, including females trained to discriminate 2.0 g/kg ethanol.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A greater proportion of the ethanol stimulus may involve receptors sensitive to 3␣-hydroxysteroids in monkeys trained to discriminate lower compared with higher doses of ethanol. In support of this hypothesis, NMDA receptors appear to mediate the discriminative stimulus effects of 2.0 g/kg ethanol in female monkeys (Vivian et al, 2002), the group showing the lowest efficacy of GABA A receptor-sensitive neuroactive steroids in this study. However, the NMDA receptor antagonist 3␣,5␤-P HS (Park-Chung et al, 1997) did not substitute for ethanol in any group, including females trained to discriminate 2.0 g/kg ethanol.…”
Section: Discussionsupporting
confidence: 78%
“…In rats, 3␣,5␤-P HS has sedative, hypnotic and anticonvulsant effects (Weaver et al, 1997), possibly due to inhibition of NMDA-induced Ca 2ϩ currents at NMDA receptors (ParkChung et al, 1997). Noncompetitive NMDA receptor antagonists partially substitute for ethanol in cynomolgus monkeys (Vivian et al, 2002). Thus, to address neuroactive steroid-sensitive NMDA receptor contributions to the discriminative stimulus effects of ethanol, the current study evaluated the substitution of 3␣,5␤-P HS for ethanol.…”
mentioning
confidence: 99%
“…Although a role for glutamate activity in mediating ethanol drinking, particularly in the context of dependence, is not fully understood, evidence from preclinical and clinical investigations suggests that glutamate transmission may significantly contribute to motivational processes that regulate ethanol consumption. For example, NMDA glutamate receptor antagonism has been reported to mimic the subjective stimulus (intoxicating) effects of ethanol in humans (Krystal et al, 2003), monkeys (Vivian et al, 2002), and rodents (Hodge et al, 2006), and animal studies have shown that metabotropic glutamate receptor-5 (mGluR5) activity in the nucleus accumbens (NAc) has a key role in mediating this effect (Besheer et al, 2009). The NAc is a critical brain structure involved in regulating motivated behaviors, and it is an important site for ethanol-glutamate interactions.…”
Section: Introductionmentioning
confidence: 99%
“…As such, activation of mGlu2/3 receptors decreases the synaptic availability of glutamate, allowing for 'refinement' of glutamatergic neurotransmission (Schoepp, 2001;Pinheiro and Mulle, 2008). Given the functional role of mGlu2/3 receptors in modulating glutamate release and that the discriminative stimulus effects of alcohol are generally characterized by processes that reduce/inhibit glutamatergic neurotransmission (Kostowski and Bienkowski, 1999), such that N-methyl-Daspartic acid (NMDA) antagonists and g-aminobutyric acid type A (GABA A )-positive modulators produce alcohol-like discriminative stimulus effects (Jarbe and McMillan, 1983;Schechter et al, 1993;Ator et al, 1993;Bienkowski et al, 1997;Hundt et al, 1998;Grant et al, 2000;Shelton and Grant, 2002;Vivian et al, 2002;Helms et al, 2009), we hypothesized that mGlu2/3 receptors may have a modulatory role in the expression of the discriminative stimulus effects of alcohol. Further support for this hypothesis comes from studies showing that mGlu2/3 receptors are highly expressed in limbic brain regions (Petralia et al, 1996;Ohishi et al, 1998;Ferraguti and Shigemoto, 2006) known to modulate the discriminative stimulus effects of alcohol, such as the nucleus accumbens and the amygdala (Hodge and Aiken, 1996;Hodge and Cox, 1998;Hodge et al, 2001;Besheer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%